Borderless Knowledge
IX, 193 p.
Keywords: Processes of knowledge production and dissemination are increasingly set in an international context. In research and higher education the links between local actors and the international environments are both proliferating and intensifying. Individual level self-organised international collaboration is increasingly supplemented by national and supranational organised activities, and by market oriented activity with a global scope. Starting from these observations, this book analyses patterns of internationalisation comprising the national and supranational level, the level of higher education institutions and private companies, as well as the level of individual researchers and graduates. As a laboratory for studying internationalisation the book uses the case of Norway, a small knowledge system set in an open society, political system and economy. The case offers exceptionally good data on the developments in its research and higher education system that record changes over time and across the different parts and levels of a national knowledge system.